THE ROLE OF DIGITALIZATION AND THE WORK ENVIRONMENT ON THE PERFORMANCE OF EMPLOYEES OF THE LIBRARY AND ARCHIVES SERVICETHE ROLE OF DIGITALIZATION AND THE WORK ENVIRONMENT ON THE PERFORMANCE OF EMPLOYEES OF THE LIBRARY AND ARCHIVES SERVICE - Aditya Asep Kurniawan; Aji Tuhagana; Dini Yani (Jurnal Ekonomi, 2022)
Digitization of archives plays an important role in an agency that is very helpful for the work of the archival service to make it easier to find lost archival documents. The Karawang Library and Archives Office created an application called Subang Larang for digitizing the archive. One form of new media archive storage is digital media using computers which must be facilitated by agencies so that the work environment becomes more effective when working. The portion and position of employees that must be considered in carrying out work so that employees will be responsible for their work and employees will achieve the results of their work. The researcher gave the title "The Role of Digitalization and Work Environment on the Performance of Employees of the Library and Archives Service". This research is descriptive and qualitative. The results show that digitizing archives is one way that helps archive services become more effective for certain interests in just a short time